SISTEM PENSETEKSI KEBOCORAN GAS DAN API DENGAN MENGGUNAKAN SENSOR MQ2 DAN FLAME DETECTOR - Jumblath, Kamal; Abdulloh, Joko (Sekolah Tinggi Teknologi 10 Nopember, 2018)
The use of LPG as a cooking material has been very lazin in society, because it is known more efficient when compared to kerosene. LPG has Advantages and disadvantages compared to kerosene. Excess LPG is more flammable for cooking and practical in its use but LPG has an explosive deficiency when there is a spark in the surrounding area. LPG tube leakage has also become one of the causes of fire among the community, to prevent the occurrence of fire A gas and apocalypse detector is manufactured by using MQ2 sensor and flame detector to prevent fire and we can know the level of LPG in the air. Detector using microcontroller based MQ2 sensor ATMega328 is a tool made to be able to know the condition (leaking or not) LPG tube. This task generates data detected by the sensors displayed by the LCD. Flame detector using Arduino uno board, ATMega328 Microcontroller as its brain, MQ2 sensor as data input, buzzer, DC fan, and LCD Metogology of data collection in the manufacture of gas and fire leak detector by using flame detector and MQ2 sensor can be from datasheet, journal, book and article and some internet sites that support the manufacture of this device. In the manufacture of gas leak detection equipment is also divided into two namely first to make hardware (hardware) and also software (softwere) The result of this device detection  is maximum limit so that sensor can avoid existence of fire caused by leaking LPG tube. Conclusions that can be drawn from the gas leak detection system and fire using MQ2 sensor and flame detector can be known by the sensor MQ2 and displayed kelayar LCD, Hidupbya buzzer and fan